G Scattered Data Interpolation with Minimized Sum of Squares of Principal Curvatures - Saaban, A.; Piah, A. R. M.; Majid, A. A.; Chang, L. H. T. (2005)
One of the main focus of scattered data interpolation is fitting a smooth surface to a set of non-uniformly distributed data points which extends to all positions in a prescribed domain.